The Contribution of Culinary on Halal Tourism: Case Study of Pekalongan City, Central Java, Indonesia - Ismanto, Kuat; Rofiq, Ahmad; Mashudi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The purpose of this paper is to identify and explore the role of culinary in the development of halal tourism. Two types of data are needed in this study, namely primary and secondary data. Primary data were collected through observation and interviews. Observations were carried out in several culinary centers. Interviews were conducted with five interviewees determined by purposive sampling. The data obtained were analyzed with content analysis and theme analysis to answer research questions. The results of this study show that Pekalongan City is feasible to become a halal tourism destination because the tourism component has met the criteria. The existence of culinary as a tourism amenity has contributed to halal tourism. Furthermore, the existing culinary can be a tourist attraction in itself. Both restaurants and small business actors provide halal guarantees on culinary, provided through certificates and seller guarantees. On the other hand, tourists have a good perception of Pekalongan City's cuisine, both of the variety of food, halal guarantees, and others. However, these conditions need to be improved to realize the visit's satisfaction and loyalty. The existence of culinary tourism explicitly needs to be fostered to support halal tourism in Pekalongan City. For this reason, local government policies must issue regulations on culinary as a destination to support halal tourism related to halal assurance.